ANALISIS PERSEPSI MASYARAKAT TERHADAP PERAN LEMBAGA PEMASYARAKATAN DALAM PEMBINAAN NARAPIDANA - Gumelar, Dian Rachmat (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2024)
This writing aims to determine public perception of correctional institutions. The research method used is qualitative with a descriptive-analytic approach. Based on the findings of this research, it shows that the public still perceives that the rehabilitation process for inmates is still not running optimally. In fact, the public is always waiting for concrete actions/firm actions from the government in line with efforts to eradicate crime in Indonesia, which is becoming more and more rampant. The supporting and inhibiting factors in the rehabilitation of inmates in correctional institutions are as follows: a. Supporting Factors 1) Correctional institution officers who are friendly to inmates and disciplined. 2) Skill development conducted based on the potential of inmates so that the rehabilitation objectives are based on the needs of inmates. 3) Good cooperation between correctional officers and related parties in the rehabilitation carried out in correctional institutions. 4) The existence of rehabilitation assistance provided by the outside community such as Social Institutions, Community Organizations, and University Students. Furthermore, the Inhibiting Factors are as follows: 1) Sometimes there are still inmates who pay less attention during the rehabilitation process. 2) There is still a lack of correctional officers who are experts in one field of rehabilitation, for example in psychological rehabilitation where there are no correctional officers who are experts in that field. 3) There are still not many supporting facilities and infrastructure in rehabilitation that support the rehabilitation process.